《新加坡初级学院学生汉字书写错别字类型及成因分析 = Analysis of writing errors in standard Chinese characters among Singapore Junior College students - 吕沭缘 Loo, Shu Yuan (Nanyang Technological University, 2022)
书写规范汉字是新加坡教育部对学生的学习目标及考核项目之一，但无论学生 处于哪个学习阶段，汉字书写偏误的数量不在少数。过去学术界对新加坡初级学院学 生的汉字书写问题并没有较完整且深⼊的研究。因此，本文的目的是进⼀步调查新加 坡初级学院生书写中错别字的情况并进行分析。 本研究主要是以归类并分析学生作文里出现的错别字为主。 笔者从数据分析发现新加坡初级学院生书写别字的比例高于错字，犯错率最高 的是音近别字。接着，本文也对中国高中生书写偏误的大体趋势和新加坡初级学院生 的进行对比，探讨两国学生之间的异同之处。结果显示两者之间的共同点在于书写同 音、音近别字的频率最高。此外，本研究也发现新加坡初级学院生的作文中常常出现 以汉语拼音和英语词汇替代规范汉字的现象。最后，笔者结合一些具有代表性的错别 字偏误例子，探讨新加坡初级学院生书写错别字的原因。 关键字：新加坡华语 初级学院 错别字 Being able to recognise and write Chinese characters correctly is expected of students taking Mandarin in Singapore. It is also one of the graded components in tests and examinations. However, it has been observed that the number of errors made lies on the high end regardless of the age groups of the students. Furthermore, there has yet to be an in-depth study of the writing of Chinese characters among Singapore Junior College students. Therefore, the purpose of this thesis is to further analyse the writing of Chinese characters by Junior College students in Singapore. This research is mainly based on the analysis and classification of errors of Chinese character writing in students' compositions. This study found that the proportion of writing homophones as well as words that are glyphically or phonologically similar (or 别字 biézì) is higher than that of wrong words (or 错字 cuòzì). This study also compares the general trend of writing errors among Chinese high school students and Singapore Junior College students, exploring the similarities and differences between the students in the two countries. The results show that writing homophonic and similar words is the most frequently seen error in both groups of students. In addition, this study also found that Singapore Junior College students often used Chinese Hanyu Pinyin and English vocabulary in place of standard Chinese characters in their compositions. Finally, this study will discuss the reasons as to why Singapore Junior College students make writing errors. Keywords: Singapore Mandarin, Junior College, Writing Errors, Chinese Characters